Tahlîlu al-Asâlîb al-Lughawiyyah li A'dhâi Firqati al-Munâdharah al-'Ilmiyyah bi Tarbiyatil Mu'allimîn al-Islâmiyyah fî Musâbaqati al-Munâdharah al-'Ilmiyyah - YAKIN, AINUL; Al-Haq, Seif Robeth (IAIN Madura, 2023)
This research is motivated by the researcher's interest in the widespread phenomenon of using rhetorical language styles, namely the use of words in speaking and writing to convince or influence listeners or readers. This study focuses on the analysis of the style of language used by members of the Arabic debate group. This study uses a qualitative approach with a descriptive-analytic type. The primary data source was taken from the documentation of 22 video debates recorded during the Arabic language debate competition which was participated in by the TMI Al-Amien Prenduan students' debate group both at the national and international levels. Researchers carried out a series of steps in analyzing data starting from reducing data, presenting data, and realizing data. The results of this study indicate that; 1) There are 26 language styles with 369 variations used by the debate groups; 2) Each style of language and its variations have their own purpose. The results of this study can be the main reference for researchers in the field of Arabic.